Return of the rishi a doctor's story of spiritual transformation and ayurvedic healing - Chopra, Deepak (Houghton Mifflin Company, 1991)
A remarkable first-person account of a young doctor's spiritual journey. Chopra guides us from his beginnings in India, through the conventional training of a Western physician, to his discovery of the ancient traditions of India's Ayurveda and the dimension of the mind in medicine.